Sediment Bacteria in the Alpine Lake Sayram: Vertical Patterns in Community Composition - Keqiang Shao; Boqiang Qin; Jianying Chao; Guang Gao (Microorganisms, 2023)
Bacterial communities inhabiting alpine lakes are essential to our understanding of ecosystem processes in a changing climate, but little has been reported about the vertical patterns of sediment bacterial communities in alpine lakes. To address this knowledge gap, we collected the 100 cm long sediment core from the center of Lake Sayram, the largest alpine lake in Xinjiang Uygur autonomous area, China, and used 16S rRNA gene-targeted amplicon sequencing to examine the bacterial populations. The results showed that bacterial diversity, as estimated by the Shannon index, was highest at the surface (6.9849 at 0–4 cm) and gradually decreased with depth up to 3.9983 at 68–72 cm, and then increased to 5.0927 at 96–100 cm. A total of 56 different phyla and 1204 distinct genera were observed in the sediment core of Lake Sayram. The bacterial community structure in the sediment samples from the various layers was dissimilar. The most abundant phyla in alpine Lake Sayram were Proteobacteria, Firmicutes, and Planctomycetes, accounting for 73%, 6%, and 4% of the total reads, respectively; the most abundant genera were Acinetobacter, Hydrogenophaga, and Pseudomonas, accounting for 18%, 12%, and 8% of the total reads, respectively. Furthermore, the relative abundance of Acinetobacter increased with sediment depth, while the relative abundance of Hydrogenophaga and Pseudomonas decreased with sediment depth. Our findings indicated that the nitrate-reducing bacteria (Acinetobacter, Hydrogenophaga, and Pseudomonas) may be prevalent in the sediment core of Lake Sayram. Canonical correspondence analysis showed that carbonate and total organic carbon (TOC) may be the main environmental factors affecting the vertical patterns of bacterial community composition (BCC) in the sediment of Lake Sayram. This work significantly contributes to our understanding of the BCC of sediments from alpine lakes in arid and semiarid regions.